Gaya Kepemimpinan Kepala Desa Cilampunghilir Kecamatan Padakembang Kabupaten Tasikmalaya dalam Pelaksanaan Pemerintahan Desa - Eman Sulaeman; Kiki Endah; Regi Refian Garis (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to identify and analyze the leadership style of the Cilampunghilir Village Head in implementing village governance. The study used a descriptive qualitative approach, with data collected through interviews, observation, and documentation. Informants were selected purposively, including the village head, village secretary, village officials, hamlet heads, and relevant community leaders. Data analysis was conducted using an interactive model that included data reduction, data presentation, and conclusion drawing. The results show that the village head's leadership style tends to be democratic and participatory. The village head emphasizes collective decision-making by prioritizing consensus through deliberation and encouraging citizen involvement in every step of governance. In decision-making, the village head strives to involve the wider community so that policy outcomes are well-received. In terms of motivation, the village head actively provides encouragement, rewards, and builds reciprocal cooperation with village officials and residents. He recognizes the importance of appreciation and trust in order to build a cooperative work environment. Furthermore, in communication, the village head is known for being open, accessible, and willing to listen to the aspirations of villagers. In terms of controlling subordinates, the village head provides clear direction, delegates tasks according to competence, and enforces discipline to ensure the smooth implementation of village programs. This indicates a leadership style that balances authority with empowerment. However, the study also identified several weaknesses, including a lack of representation of marginalized groups, low frequency of outreach activities, and unequal access to information. Therefore, it is recommended that deliberation forums be strengthened with a more inclusive approach, diversified outreach methods through the use of digital channels, and increased transparency be implemented to optimize village governance.